Brass for electrical connector and preparation method thereof

By adjusting the content of copper, lead, zinc, manganese and silver, and using multi-process alloy preparation method, the shortcomings in the mechanical and elastic properties of existing lead brass alloys are solved, and brass alloys for high-performance electrical connectors are realized. Prepared, with high strength, good elasticity, bending resistance, excellent conductivity and cutting performance.

CN116287854BActive Publication Date: 2025-02-18JINTIAN COPPER GROUP CORP NINGBO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310223546.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2025-02-18
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

Existing lead brass alloys are difficult to take into account high strength and high plasticity in terms of mechanical properties and elastic properties, and the conductive and cutting properties are not sufficient to meet the needs of high-performance electrical connectors.

Method used

Cu: 65 to 70 wt%, Pb: 0.2 to 1.0 wt%, Mn: 0.01 by adjusting the weight percentage of copper (Cu), lead (Pb), zinc (Zn), manganese (Mn) and silver (In). ~0.1 wt%, In: 0.01 to 0.2 wt%, brass alloy is used, and semi-continuous casting, hot extrusion, disk drawing, annealing and low-temperature annealing are used to optimize the microstructure and performance of the alloy.

Benefits of technology

It realizes the high strength, good elasticity, bending resistance, excellent conductivity and cutting performance of brass alloys to meet the needs of high-performance electrical connectors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116287854B_ABST
    Figure CN116287854B_ABST
Patent Text Reader

Abstract

A brass for an electrical connector, characterized in that it comprises the following components in weight percentage: Cu: 65-70wt%; Pb: 0.2-1.0wt%; Mn: 0.01-0.1wt%; In: 0.01-0.2wt%; the remainder is Zn and unavoidable impurities, so that the mechanical properties and elastic properties of the brass for the electrical connector are better. The present invention also relates to a method for preparing the brass for the electrical connector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to copper alloy processing, in particular to brass for an electric connector, and also to a preparation method of the brass for the electric connector. Background Art

[0002] Copper alloy is an alloy with pure copper as the base and one or more other elements added. Copper alloys are generally divided into three categories according to the alloy system: brass, bronze and nickel silver. Among them, brass is an alloy composed of copper and zinc. Brass alloy has good mechanical properties, corrosion resistance, hot and cold processing properties, and low cost of use. Therefore, brass alloy is often used to process and prepare electrical connectors such as pins and sockets.

[0003] Due to the complexity of the application environment of electrical connectors, the performance requirements for brass used in electrical connectors are as follows:

[0004] 1. Higher mechanical properties need to meet the requirements of resistance to plastic deformation under long-term use conditions. The brass base material is sawn and precision-processed, and then assembled with other accessories into corresponding objects. The resulting assembly must undergo roller and drop tests before being put into use. If the brass base material end material is deformed after roller and drop tests, it cannot meet the use requirements. Generally, the larger the mass of the test object, the higher the strength requirement for the base material brass. Calculated based on a 200g object, the tensile strength of the brass base material must be no less than 600MPa, and the hardness must be no less than 190HV to stably meet the above-mentioned tensile strength and hardness test performance requirements.

[0005] 2. Good elasticity and bending resistance. Generally, the pins are required to maintain good elasticity after tens of thousands of plugging and unplugging. Therefore, while ensuring that the brass base material has good elasticity, it must also have good bending plasticity to avoid brittle cracking of the material. Generally, the processed brass base material will be subjected to a 90° bending test. If cracks or breaks appear after bending, it is unqualified. Therefore, in order to stably achieve the above performance, the base material elastic modulus must be no less than 120GMa, and the elongation A must be no less than 8%.

[0006] In addition, considering the processing and application of brass in electrical connectors, brass alloys also need to have good cutting performance and electrical conductivity.

[0007] In order to improve the performance of brass alloys to meet the application of specific working conditions, some functional elements are usually added to copper-zinc alloys to form multi-element brass alloys, such as adding lead elements to copper-zinc alloys to form lead brass, and adding silicon elements to copper-zinc alloys to form silicon brass. Lead brass has the mechanical properties, corrosion resistance, and hot and cold processing properties of ordinary brass. In addition, because lead exists in the alloy as free lead particles, the cutting chips are in the form of foam during the cutting process. After high-speed cutting, a very smooth surface can be obtained. Compared with lead-free brass, it has better cutting performance and elastic properties. Although the cutting performance of silicon brass is close to that of lead brass, the silicon element is extremely unfavorable for electrical conductivity. At the same time, silicon will significantly increase the brittleness of the material and is not conducive to bending resistance. Therefore, lead brass is more suitable as a material for electrical connectors.

[0008] The commonly used lead brass grades on the market are C3601, C3602, and C3604. Although they have good cutting performance, their elastic modulus is generally only 110GPa, which is difficult to meet the performance requirements of high-performance pins with high elasticity. Moreover, the aforementioned lead brass mainly uses work hardening to improve its strength, and its tensile strength is difficult to effectively exceed 600MPa. Even if the strength exceeds 600MPa through extreme deformation, under this condition, the material is brittle and the elongation is generally less than 2%. Therefore, the aforementioned lead brass cannot have both high strength and bending resistance. Summary of the invention

[0009] The first technical problem to be solved by the present invention is to provide a brass for an electrical connector with better mechanical properties and elastic properties in view of the above technical status quo.

[0010] The second technical problem to be solved by the present invention is to provide a method for preparing the brass for the electrical connector in view of the above technical status.

[0011] The technical solution adopted by the present invention to solve the first technical problem mentioned above is: a brass for an electrical connector, characterized in that it includes the following components in weight percentage: Cu: 65-70wt%; Pb: 0.2-1.0wt%; Mn: 0.01-0.1wt%; In: 0.01-0.2wt%; the balance is Zn and unavoidable impurities.

[0012] The lower limit of Cu element is controlled at 65%, in order to ensure the formation of more α phase. If the Cu element content is too low, the added Zn surplus will increase, thereby forming more hard and brittle β phase. A high β phase content will increase the brittleness of the material, which is not conducive to making the material have both high strength and high plasticity. At the same time, too low Cu content is not conducive to improving the electrical conductivity of the material. The upper limit of Cu element is controlled at 70%. If the Cu element content is too high, the deformation resistance of the alloy during hot extrusion processing will be significantly increased, making it difficult to extrude normally. Further increasing the extrusion temperature can reduce the extrusion deformation resistance to a certain extent, but the alloy of the present invention also contains hot brittle elements such as Pb and P, so the extrusion temperature should not be set too high. In summary, in order to ensure that the alloy has high strength, high plasticity and high conductivity, and at the same time ensure that the alloy has good hot extrusion plasticity, it is necessary to strictly control the Cu content in the range of 65-70%.

[0013] The main function of the Pb element is to improve the cutting performance of the material. The lower limit of the Pb element content is controlled at 0.2% to ensure the formation of more easy-to-cut phases and improve the cutting performance of the material. The upper limit of the Pb element content is controlled at 1%. On the one hand, it reduces the effect of excessive Pb content on the hot brittleness of the alloy during extrusion; on the other hand, excessive Pb content is not conducive to improving the mechanical properties of the alloy, increases the brittleness of the material, and cannot obtain ideal mechanical properties through large deformation work hardening.

[0014] Preferably, the brass microstructure contains α phase and Mn-In strengthening phase, the α phase accounts for 90-99%, and the Mn-In strengthening phase accounts for 9-1%. The α phase ratio is controlled at 90-99% for the purpose of improving the plasticity of the material and improving the bending resistance. The Mn-In strengthening phase ratio is controlled at 1-9%. If the Mn-In strengthening phase ratio is too low, the mechanical properties and elastic properties of the material will not be significantly improved; if the Mn-In strengthening phase ratio is too high, the brittleness of the material will increase, and cracking will easily occur during the processing process. At the same time, if the Mn-In strengthening phase ratio is too high, it will reduce the mechanical properties and elastic properties of the material.

[0015] Preferably, the average size of the Mn-In strengthening phase is 0.01-1 μm, and the average size of the α phase is 10-30 μm. Both too large and too small average size of the Mn-In strengthening phase are not conducive to improving the strength and elastic properties of the material. If the average size of the α phase is too small, it is not conducive to improving the bending resistance; if the average size of the α phase is too large, it is not conducive to improving the cutting performance and mechanical properties.

[0016] In order to further improve the material and cutting performance, the component also includes 0.01-0.03wt% P. The main function of the P element is to refine the lead particle size and achieve a larger number of dispersed distribution of Pb particles, thereby further improving the material cutting performance. Because the alloy of the present invention has a lower added Pb content than ordinary lead brass, in order to achieve the same ideal cutting performance, under a certain Pb content, it is necessary to further increase the number of lead particles distributed on the α grain boundary. Therefore, reducing the size of the generated lead particles and effectively increasing the number of lead particles are the main means of improving the cutting performance of the present invention. The lower limit of the P element content is controlled at 0.01wt%. If the P content is low, the above-mentioned improvement effect is not significant; the upper limit of the P element content is controlled at 0.03wt%. If the P content is too high, on the one hand, the improvement effect on the cutting performance is not significant; on the other hand, it will greatly increase the brittleness of the material, affect the cold and hot processing deformation, and also reduce the electrical conductivity.

[0017] In order to optimize the cutting performance of the brass alloy material, the average size of the Pb particles is 0.1 to 2 μm, and 1 mm 2 The number of Pb particles per unit area is 10,000 to 30,000. If the average size of the Pb particles is too small, the improvement in cutting performance is not obvious; if the average size of the Pb particles is too large, the distribution of the Pb particles will be reduced, and the cutting performance of the material will also be reduced. The more Pb particles there are, the better the cutting performance of the material. If the number is too small, it is not conducive to improving the cutting performance of the material; and 30,000 reaches the upper limit of the number of Pb particles formed by the composition and process of the present invention.

[0018] Preferably, the component also includes at least one of Zr, Pr, and La, with a total amount of 0.01 to 0.08 wt%. Elements such as Zr, Pr, and La can assist in improving the mechanical properties, bending resistance, and electrical conductivity of the material. The addition of the Zr element can further improve the high temperature resistance and mechanical properties of the material. The Zr element plays a certain precipitation strengthening role after the heat treatment process. At the same time, Zr can effectively reduce the strength attenuation of the material under high temperature conditions, ensuring that the material maintains a high strength during use in a high temperature environment. If the Zr content is added too high, the casting stress of the material will increase, and the ingot produced will be very easy to crack. Pr and La elements have similar effects. On the one hand, they play a purifying role in the casting process, achieve a good impurity removal effect, and are conducive to the material obtaining good electrical conductivity and bending resistance plasticity. On the other hand, the diffusion of the Pb element is further promoted, which is conducive to the dispersion and distribution of Pb particles in the alloy, and the cutting performance of the material is further improved.

[0019] Preferably, the brass has a hardness of 200-260 HV, a tensile strength of 620-700 MPa, an elongation of 8-15%, an elastic modulus of 120-130 MPa, and a conductivity of 20-35% IACS.

[0020] The technical solution adopted by the present invention to solve the above-mentioned second technical problem is: a method for preparing brass for an electrical connector, characterized in that it comprises the following steps in sequence:

[0021] 1) Melting: Prepare the materials according to the required components and their contents, and the melting temperature is 950-1050℃.

[0022] 2) Casting: The semi-continuous casting process is used to produce ingots, the casting temperature is 1050-1150°C, the cooling water pressure is 0.3-1.0MPa, the water inlet temperature is 10-20°C, and the water outlet temperature is 20-40°C;

[0023] 3) Extrusion: the extrusion heating temperature is 720-800°C, the extrusion heating time is 2-4h, the extrusion ratio is 300-700:1, and the extrusion speed is 5-10mm / s;

[0024] 4) Coil drawing: The extruded billet is subjected to a drawing process after pickling, and the coil drawing processing rate is 25-40%.

[0025] 5) Annealing: The billet after coil drawing is subjected to annealing heat treatment, the annealing heating rate is 10-30°C / min, the holding temperature is 420-470°C, and the holding time is 150-500°C;

[0026] 6) Drawing: After pickling, the annealed blank is placed in a combined drawing device for drawing. The drawing processing rate is 15-25% and the drawing rate is 30-100 m / min.

[0027] 7) Low temperature annealing: Place the drawn bar in a box furnace for low temperature annealing. The low temperature annealing heating rate is 2-10°C / min, the holding temperature is 120-200°C, and the holding time is 200-700min;

[0028] 8) Straightening: After the annealed bar is pickled with weak acid, it is straightened;

[0029] 9) Finished product inspection: Finished bar performance testing and packaging for storage.

[0030] In the above step 2) of the casting process, if the casting temperature is too low, the fluidity of the molten metal will be poor during solidification, and defects such as cold shut will be easily formed after casting; if the casting temperature is too high, the content of easily burnt elements such as Zn and P will be reduced, and the melt will easily absorb air under extremely high temperature conditions, thereby increasing the risk of forming porosity defects in the ingot.

[0031] In the above step 2) casting process, the parameter design of cooling water pressure, water inlet temperature and water outlet temperature can control the primary cooling rate. If the cooling rate is too slow, it is easy to cause molten copper to not completely solidify in the crystallizer, and molten copper is easy to flow out of the crystallizer during the casting process and leak copper, affecting normal casting production. If the cooling rate is too fast, molten copper solidifies quickly in the crystallizer, the solidification liquid level rises, and the contact area between the ingot and the crystallizer after solidification is increased, thereby increasing the casting friction, thus reducing the surface quality of the ingot, and as the cooling intensity increases, the surface quality deteriorates more seriously.

[0032] In the casting process of step 2) above, when the casting starts, the casting speed is controlled at 0.5-1m / h. Since it takes a certain amount of time for the molten copper to enter the crystallizer and complete the filling when the casting starts, a slower casting speed needs to be adopted. If the casting speed is too slow, the solidification liquid level of the ingot in the crystallizer will rise, increasing the friction with the crystallizer and causing the surface quality to decrease; if the casting speed is too fast, insufficient cooling may occur and copper leakage may occur. After stabilizing 1 / 4 of the total length of the cast ingot, the casting speed can be increased to 1-3m / h. If the casting speed is too slow, the solidification liquid level of the ingot in the crystallizer will rise, increasing the friction with the crystallizer and causing the surface quality to decrease; if the casting speed is too fast, insufficient cooling may occur and copper leakage may occur.

[0033] In the above step 3) of the extrusion process, if the extrusion heating temperature is too low, the alloy has low hot deformation plasticity and cannot be extruded normally; if the extrusion heating temperature is too high, on the one hand, the ingot is overburned, the grains grow, and the extrusion structure is uneven. On the other hand, under high temperature heating conditions, the material is very easy to dezincify, and dezincified holes are easily formed on the surface of the billet after extrusion.

[0034] If the extrusion heating time is too short, the ingot is not heated sufficiently and the temperature near the center of the ingot is not effectively raised to the required temperature; if the extrusion heating time is too long, the ingot is heated for a long time and the degree of dezincification on the surface increases.

[0035] If the extrusion ratio is too small, the ingot will not be fully deformed during extrusion, and the as-cast structure will be easily retained, while the uniformity of the structure will be average. If the extrusion ratio is too large, the required extrusion force will exceed the equipment limit, and problems such as extrusion die breakage and extrusion blockage will easily occur.

[0036] If the extrusion speed is too low, the extrusion time will increase. Since the ingot temperature decreases during the extrusion process, when the ingot is extruded to the tail, the temperature will drop suddenly and the extrusion force will increase rapidly. When the extrusion force exceeds the equipment limit, the extrusion will stop. If the extrusion speed is too high, the deformation heat generated during the extrusion process will increase. Excessive deformation heat will cause secondary heating of the ingot, so that the actual extrusion temperature is higher than the required set temperature.

[0037] In the above step 4) of the coiling process, the processing rate is controlled at 25-40% to achieve sufficient damage to the extruded billet grains and effectively reduce the recrystallization temperature of the material. Controlling the above processing rate is conducive to achieving softening at a lower temperature in the subsequent annealing process, avoiding setting the annealing temperature too high to cause the Pb particles to aggregate and reduce the material cutting performance, and a larger processing rate coiling can further improve the uniformity of the billet performance.

[0038] In the above step 5) annealing process, if the annealing heating rate is too fast, the outer ring of the blank will be overheated, which is not conducive to the uniform heating of the blank, resulting in differences in the performance of the outer and inner rings; if the heating rate is too slow, although it is conducive to the uniform heating of the blank, it will greatly increase the time and affect the production efficiency. If the annealing temperature is too low, the plasticity of the material will be low, affecting the bending resistance of the finished product; if the annealing temperature is too high, on the one hand, it will cause Pb particles to aggregate, affecting the cutting performance of the material. On the other hand, it will cause the material to soften excessively, and the strength, hardness and elastic properties will all decrease. If the annealing time is too short, the annealing is insufficient, the material cannot be fully softened, and the drawing performance of the finished product is affected; if the annealing time is too long, the number of Pb particles will decrease and the cutting performance of the material will decrease.

[0039] In the above step 6), if the drawing rate is too low, the material will not be fully hardened and the strength will not reach the ideal condition; if the drawing rate is too high, the plasticity of the material will be reduced, affecting the bending resistance of the final product. If the drawing rate is too low, the production efficiency will be affected. If the drawing rate is too high, the material stress distribution will be uneven.

[0040] The low-temperature annealing process in the above step 7) can further increase the plasticity and electrical conductivity of the material. If the heating rate is too low, the production efficiency will be affected; if the heating rate is too high, it will easily cause the material near the heating source to heat too quickly, while the material far from the heating source will heat slowly, resulting in different uniformity of the performance of the whole batch of materials. If the insulation temperature is too low, the annealing effect is insufficient. On the one hand, the plasticity of the material cannot be effectively improved, which affects the bending resistance of the product. On the other hand, the material stress is not sufficiently eliminated, and the electrical conductivity of the finished product cannot be further improved; if the insulation temperature is too high, although the plasticity of the material is significantly improved, it will cause a significant decrease in strength, so that the finished product cannot have both high strength and high plasticity. If the insulation time is too low, the low-temperature annealing effect is insufficient, and the plasticity and electrical conductivity of the material cannot be further improved; if the insulation time is too long, the production cycle and cost will be greatly increased.

[0041] It is further designed that in step 2), the specification of the ingot is φ200~φ250mm, the semi-continuous casting process eliminates the secondary cooling link, and an electromagnetic stirrer is used for stirring during the casting process, and the current of the electromagnetic stirrer is 100~150A and the frequency is 20~80Hz. The ingot out of the crystallizer temperature is 500~800℃, and the average grain size of the α phase of the ingot produced by the casting process is: 20~40μm, the cross-section long columnar α phase area accounts for <10%, 1mm 2 The number of lead particles per unit internal area is 8000 to 20000, so that the surface quality of the obtained ingot is good and defect-free, and the composition and structure are uniform.

[0042] Considering the ideal extrusion ratio obtained by subsequent extrusion, the specifications of the ingots produced are in the range of φ200 to φ250. The purpose of canceling the secondary cooling is to avoid the formation of stress cracks due to uneven cooling of the outer surface and the center of the ingot. Therefore, the cross-sectional area of ​​the ingot is relatively large. If secondary cooling is performed, it takes a long time for the temperature drop to be transferred to the center after the outer layer of the ingot is cooled, which makes it easier to form stress cracks. At the same time, the brass alloy components of the present invention contain 0.01-0.1% Mn and 0.01-0.2% In. The thermal conductivity of the alloy is average. After secondary cooling, the outer layer is easily solidified while the center is not solidified. Finally, the ingot obtained is prone to form stress cracks extending from the center to the outside.

[0043] The purpose of auxiliary electromagnetic stirring technology is to refine the grains, improve the uniformity of the ingot structure, promote the dispersion of Pb particles, and improve the cutting performance of the material. If the current and frequency parameters of the electromagnetic stirrer are set too low, the above improvement effect will not be significant; if the current and frequency are set too high, the Mn-In strengthening phase will easily aggregate over a large area, which will reduce the uniformity of the mechanical properties and organizational properties of the ingot.

[0044] It is further designed that in step 3), after the billet flows out from the extrusion die, it flows out to the take-up reel through the graphite conduit, and the billet is cooled in the graphite conduit with nitrogen to a surface temperature of 500-600°C, and the cooling rate of the billet in the take-up reel is 50-100°C / h.

[0045] After the billet flows out of the extrusion die, it needs to be cooled by blowing nitrogen before flowing out through the graphite tube to the take-up reel. It is required to control the extruded billet in the graphite tube within the time range of 1 to 4 seconds, and the surface temperature of the extruded billet is quickly cooled to 500-600℃. The purpose of the above operation is: since the extrusion deformation plasticity of this alloy is lower than that of common lead brass, the extrusion temperature is set higher. If the high-temperature extruded billet is not cooled by nitrogen in the graphite tube, the surface of the extruded billet is prone to dezincification and the formed zinc oxide accumulates in the graphite tube. On the one hand, dezincification holes are formed on the surface of the extruded billet, and on the other hand, the accumulated zinc oxide solids further scratch the surface of the soft extruded billet. The advantages of using nitrogen blowing: on the one hand, it is an inert gas that will not cause excessive oxidation on the surface of the high-temperature extruded billet. On the other hand, nitrogen blowing can realize the cleaning of the inside of the graphite tube to avoid excessive accumulation of zinc oxide and scratches on the surface of the extruded billet. The extruded billet is cooled to 500-600℃ in the graphite tube, and dezincification can be effectively avoided at this temperature. If the temperature is too low, it means that the cooling is too fast. Too fast cooling will promote the formation of brittle β phase, which is not conducive to improving the bending plasticity of the material; if the temperature is too high, it means that the cooling effect is not good and the dezincification problem on the surface of the extruded billet cannot be effectively improved.

[0046] The cooling speed of the extruded billet in the take-up drum needs to be controlled at 50-100℃ / h. This process mainly realizes the slow cooling of the extruded billet from 500-600℃ to room temperature. If the cooling speed is too slow, it will affect the production efficiency; if the cooling speed is too fast, the high-temperature β phase in the extruded billet will not have time to complete the phase transformation to α phase. The residual β phase of the extruded billet is not conducive to improving the bending plasticity of the material.

[0047] Compared with the prior art, the advantages of the present invention are:

[0048] ① The brass for electrical connectors improves mechanical and elastic properties by adding 0.01-0.1wt% of Mn elements. If the Mn content is lower than 0.01wt%, the Mn element has no significant effect on improving mechanical and elastic properties. If the Mn content is higher than 0.1wt%, too much Mn-containing hard phase will be formed. Although the mechanical properties are improved, the plasticity of the alloy material will be reduced, the bending resistance will be reduced, and the electrical conductivity will also be affected.

[0049] ②By adding 0.01-0.2wt% of In element to brass for electrical connectors, not only can the plasticity of the material be improved, but also good bending plasticity under the premise of high strength, and the critical current density of the material can be increased, thereby improving the conductivity. More importantly, the In element combines with the Mn element to form a Mn-In strengthening phase, which plays a role in precipitation strengthening, thereby further increasing the strength of the alloy and improving the elastic properties. If the In element content is less than 0.01wt%, the improvement effect of the In element on the mechanical properties, elastic properties, bending plasticity, and electrical conductivity is not significant. If the In element content is higher than 0.2wt%, the material strength and electrical conductivity will be reduced, and the material processing plasticity will also be reduced accordingly.

[0050] ③ The content of Pb in brass for electrical connectors is controlled at 0.2-1.0wt%. If the content of Pb is lower than 0.2wt%, the easy-to-cut phase formed by Pb is less, and the cutting performance is affected. If the content of Pb is higher than 1.0wt%, it will not only cause hot brittleness during extrusion of the alloy, but also be unfavorable for improving the mechanical properties of the alloy, increase the brittleness of the material, and fail to obtain the ideal mechanical properties through large deformation work hardening;

[0051] ④ The brass alloy rod prepared by the preparation method of brass for electrical connectors has a hardness of 200-260 HV, a tensile strength of 620-700 MPa, an elongation of 8-15%, an elastic modulus of 120-130 MPa, a conductivity of 20-35% IACS, an average size of α phase of 10-30 μm, an α phase ratio of 90-99%, an average size of Mn-In strengthening phase of 0.01-1 μm, a Mn-In strengthening phase ratio of 9-1%, and an average size of Pb particles of 0.1-2 μm; 1mm 2 The number of Pb particles per unit area is 10,000 to 30,000, so that the prepared brass rod for electrical connector has the comprehensive characteristics of high strength, high elasticity, bending resistance, easy cutting and good conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a scanning electron microscope image (5000 times) of the sample of Example 2 of the present invention;

[0053] Figure 2 This is a metallographic microscope image (500 times) of the sample of Comparative Example 2 of the present invention;

[0054] Figure 3 This is a metallographic microscope image (500 times) of the sample of Example 2 of the present invention. DETAILED DESCRIPTION

[0055] The embodiments of the present invention are described in further detail below.

[0056] The brass for the electrical connector in this embodiment is characterized by comprising the following components in weight percentage: Cu: 65-70wt%; Pb: 0.2-1.0wt%; P: 0.01-0.03%; Mn: 0.01-0.1wt%; In: 0.01-0.2wt%; the remainder is Zn and unavoidable impurities.

[0057] The method for preparing brass for an electrical connector in this embodiment is characterized by comprising the following steps in sequence:

[0058] 1) Melting: Prepare the materials according to the required components and their contents, and the melting temperature is 950-1050℃.

[0059] 2) Casting: The semi-continuous casting process is used to produce ingots, with a casting temperature of 1050-1150°C, a cooling water pressure of 0.3-1.0MPa, a water inlet temperature of 10-20°C, and a water outlet temperature of 20-40°C. The specifications of the ingots are φ200-φ250mm. At the beginning of casting, the casting speed is controlled at 0.5-1m / h. After stabilizing 1 / 4 of the total length of the ingot, the casting speed can be increased to 1-3m / h. The semi-continuous casting process eliminates the secondary cooling link and uses an electromagnetic stirrer for stirring during the casting process. The current of the electromagnetic stirrer is 100-150A and the frequency is 20-80Hz. The temperature of the ingot out of the crystallizer is 500-800°C.

[0060] 3) Extrusion: the extrusion heating temperature is 720-800°C, the extrusion heating time is 2-4h, the extrusion ratio is 300-700:1, and the extrusion speed is 5-10mm / s; after the billet flows out from the extrusion die, it flows out to the take-up reel through the graphite conduit, and the billet is cooled in the graphite conduit with nitrogen to its surface temperature of 500-600°C, and the cooling rate of the billet in the take-up reel is 50-100°C / h.

[0061] 4) Coil drawing: The extruded billet is stretched after pickling, and the coil drawing processing rate is 25-40%.

[0062] 5) Annealing: The billet after coiling is subjected to annealing heat treatment, the annealing heating rate is 10-30°C / min, the holding temperature is 420-470°C, and the holding time is 150-500°C;

[0063] 6) Drawing: After pickling, the annealed blank is placed in a combined drawing device for drawing. The drawing processing rate is 15-25% and the drawing rate is 30-100 m / min.

[0064] 7) Low temperature annealing: Place the drawn bar in a box furnace for low temperature annealing. The low temperature annealing heating rate is 2-10°C / min, the holding temperature is 120-200°C, and the holding time is 200-700min;

[0065] 8) Straightening: After the annealed bar is pickled with weak acid, it is straightened;

[0066] 9) Finished product inspection: Finished bar performance testing and packaging for warehousing.

[0067] 1. Example Preparation

[0068] 1. The ingredients are prepared according to the weight ratio of the components of each embodiment in Table 1 below, wherein the sample of Comparative Example 1 is brass with a commercial grade of H65, and the sample of Comparative Example 2 is brass with a commercial grade of C3602.

[0069] Table 1. Examples and Comparative Examples Composition Unit: wt%

[0070] Cu Pb P Mn In Zn other Example 1 68.0 0.82 0.02 0.06 0.12 Remain 0.01% Zr + 0.01% Pr Example 2 66.2 0.75 0.01 0.09 0.15 Remain 0.01%La Example 3 67.7 0.79 0.02 0.08 0.14 Remain 0.02%Pr+0.02%La Example 4 69.5 0.96 0.03 0.05 0.10 Remain 0.02%Pr+0.03%La Example 5 68.8 0.92 0.03 0.06 0.13 Remain 0.03%Pr Comparative Example 1 66.5 0.02 0.001 / / Remain / Comparative Example 2 60.2 1.8 / / / Remain 0.01%Fe+0.01%Sn

[0071] 2. Prepare each group of example samples according to the process parameters in the following steps.

[0072] Table 2. Casting process parameters of the embodiment

[0073]

[0074] Table 3. Example extrusion process parameters

[0075]

[0076] Table 4. Parameters of coil pulling, annealing, drawing, and low temperature annealing processes in the embodiment

[0077]

[0078]

[0079] 2. Performance Test

[0080] The samples of each embodiment were tested for hardness, tensile strength, elongation, elastic modulus, and metallographic microscopy. The hardness test was conducted in accordance with GB / T 4340.1-2009 Metallic Materials Vickers Hardness Test Part 1: Test Method, the tensile strength and elongation tests were conducted in accordance with GB / T 228.1-2010 Metallic Materials Tensile Test Part 1: Room Temperature Tensile Test Method, the elastic modulus test was conducted in accordance with GB / T 22315-2008 Metallic Materials Elastic Modulus and Poisson's Ratio Test Method, and the electrical conductivity test was conducted in accordance with GB / T 351-2019 Metallic Materials Resistivity Measurement Method. The metallographic microscopy test was conducted in accordance with YS / T 449-2002 Microstructure Inspection Method for Copper and Copper Alloy Castings and Processed Products.

[0081] The test results are as follows:

[0082] Table 5. Mechanical and electrical properties of the samples of the examples and the comparative examples

[0083]

[0084] It can be seen from Table 5 above:

[0085] 1) The hardness and tensile strength of the example samples are higher than those of the comparative example samples, so the example samples have better anti-deformation ability.

[0086] 2) The elongation of the example sample is higher than that of the comparative example sample, so the example sample has more excellent plasticity and good bending resistance, and will not form cracks after bending 90°.

[0087] 3) The elastic modulus of the example sample is higher than that of the comparative example sample, so the example sample has more excellent elastic performance. After being processed to the insertion pin, it still maintains high elastic performance after repeated insertion and removal, and is not prone to relaxation.

[0088] 4) The conductivity of the example sample is higher than that of the comparative example sample, so the example sample has better conductive performance.

[0089] Based on the metallographic microscopic test results, the size and area ratio of the Mn-In strengthening phase, the size of the Pb particles, and the 1mm 2 The number of Pb particles per unit area is calculated. The calculation results are shown in the following table:

[0090] Table 6. Microstructure properties of finished products of examples and comparative examples

[0091]

[0092] It can be seen from Table 6 above that in the example samples, 1 mm 2 The number of Pb particles per unit area is higher than that of the comparative sample, so the example sample has better cutting performance.

[0093] In summary, the brass for electrical connectors prepared in this embodiment has better deformation resistance, plasticity, bending resistance, elasticity, conductivity and cutting performance, and is a high-performance brass for electrical connectors.

Claims

1. A brass for an electrical connector, characterized in that: The composition includes the following weight percentages: Cu: 65-70 wt%; Pb: 0.2~1.0 wt%; Mn: 0.01~0.1 wt%; In: 0.01~0.2 wt%; the balance is Zn and unavoidable impurities; The brass microstructure contains an α phase and a Mn-In strengthening phase, wherein the α phase accounts for 90 to 99% and the Mn-In strengthening phase accounts for 9 to 1%. The average size of the Mn-In strengthening phase is 0.01-1 μm, and the average size of the α phase is 10-30 μm; The components also include 0.01-0.03 wt% of P; The average size of the Pb particles is 0.1-2 μm, and 1 mm 2 The number of Pb particles per unit area is 10,000~30,000; The brass has a hardness of 200-260 HV, a tensile strength of 620-700 MPa, an elongation of 8-15%, an elastic modulus of 120-130 MPa, and a conductivity of 20-35% IACS.

2. The brass for an electrical connector according to claim 1, characterized in that: The components also include at least one of Zr, Pr and La, with a total amount of 0.01 to 0.08 wt%.

3. A method for preparing brass for an electrical connector according to any one of claims 1 to 2, characterized in that: The steps are as follows: 1) Melting: Mix the ingredients according to the required components and their contents, and the melting temperature is 950-1050℃; 2) Casting: The semi-continuous casting process is used to produce ingots, with a casting temperature of 1050~1150℃, a cooling water pressure of 0.3~1.0MPa, an inlet water temperature of 10~20℃, and an outlet water temperature of 20~40℃; 3) Extrusion: extrusion heating temperature is 720~800℃, extrusion heating time is 2~4h, extrusion ratio is 300~700:1, and extrusion speed is 5~10mm / s; 4) Coil drawing: The extruded billet is drawn after pickling, and the coil drawing processing rate is 25~40%; 5) Annealing: The billet after coil drawing is annealed at a heating rate of 10-30°C / min and a holding temperature of 420-470°C; 6) Drawing: After pickling, the annealed blank is placed in a combined drawing equipment for drawing. The drawing processing rate is 15-25% and the drawing rate is 30-100 m / min. 7) Low temperature annealing: Place the drawn bar in a box furnace for low temperature annealing. The low temperature annealing heating rate is 2~10℃ / min, the holding temperature is 120~200℃, and the holding time is 200~700min; 8) Straightening: After the annealed bars are pickled with weak acid, they are straightened.

4. The preparation method according to claim 3, characterized in that: In step 2), the specification of the ingot is φ200~φ250mm, the semi-continuous casting process eliminates the secondary cooling step, and an electromagnetic stirrer is used for stirring during the casting process, and the current of the electromagnetic stirrer is 100~150A and the frequency is 20~80Hz.

5. The preparation method according to claim 3, characterized in that: In step 3), after the billet flows out from the extrusion die, it flows out to the take-up reel through the graphite conduit. The billet is cooled in the graphite conduit with nitrogen until its surface temperature is 500-600°C. The cooling rate of the billet in the take-up reel is 50-100°C / h.

Citation Information

Patent Citations

  • Brass alloy and preparation method thereof

    CN115386765A

  • Brass alloy

    WO2017009176A1